Light weight cementitious composites reinforced with Pinus spp. sawdust - Bilcati, Géssica Katalyne; Lengowski, Elaine Cristina; Jumes, Jessica Jayne; Andrade, Fernanda Horst; Nervis, Ingrid Rodrigues; de Souza, Isabela dos Santos Custódio; Langaro, Eloise (Cadernos de Ciência & Tecnologia, 2021)
Aggregates play an important role in concretes and mortars, as besides reducing production costs, they have a beneficial influence on the material characteristics and on its final application. This work reports experimental investigations on the use of Pinus spp. sawdust as aggregate to mortars and concretes for the production of cementitious composites. Tests for sawdust characterization were performed according to standards for aggregates used in mortars and concretes. The percentages of sawdust added in mortar and concrete varied by 10, 15, and 20%. Composites were characterized according to described mortar and concrete standards. Results obtained in the granulometry test classified the sawdust as a thick and continuous aggregate, which makes it possible to use sawdust as an aggregate in concretes. In the consistency tests, the higher is the sawdust percentage, the greater is the water demand to reach the adequate workability in mortars. For water absorption test, the addition of larger amounts of sawdust resulted in higher absorption. The addition of 15% sawdust showed better results in both the compressive strength and the consistency index.